PENGARUH LINGKUNGAN KERJA DAN KEPEMIMPINAN TERHADAP KINERJA DENGAN KEPUASAN KERJA SEBAGAI VARIABEL INTERVENING (STUDI PADA PEGAWAI DINAS TENAGA KERJADAN TRANSMIGRASI PROVINSI NUSA TENGGARA BARAT) - Hamdi, Hamdi (JMM UNRAM -UNRAM MANAGEMENT REVIEW, 2017)
This study aims to determine the effect of Work Environment and Leadership on Performance with Job Satisfaction as Intervening Variables at the Department of Manpower and Transmigration of West Nusa Tenggara Province. Population in this research is civil servant amounting to 208 employees with sampling technique that is Proportional Random Sampling amounting to 68 civil servant. This type of research is an associative research of causality. Data analysis was done with Path Analysis using SPSS program aid. The results of the analysis show that: 1) the work environment has a positive and significant effect on performance. 2) Work environment has a positive and significant impact on job satisfaction. 3) Leadership has a positive and significant impact on performance. 4) Leadership positively and significantly influence on job satisfaction. 5) Job satisfaction has a positive and significant impact on performance. 6) Working Environment and Leadership have positive and significant impact on performance through job satisfaction of personnel of NTB Provincial Manpower and Transmigration Office.Keywords: Work Environment, Leadership, Job Satisfaction and Employee Performance.